2020
DOI: 10.1021/acs.macromol.0c00060
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Poly(dendrimer)-Based Sensors for the Detection of Explosives and Taggant Vapors

Abstract: Poly(dendrimers) are an emerging class of fluorescent organic semiconductors that have been investigated for their ability to detect nitro-based explosives and taggants. In this work, the sensing chromophores were dendritic side chains attached to a norbornenylderived polymer backbone. The sensing chromophore of each poly(dendrimer) was based on fluorene and carbazole moieties, both of which have been shown to be sensitive toward nitro-containing explosives. The monomers, and corresponding polymers, were scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Graphene‐based sensors were demonstrated that platforms were designed to incorporate pristine graphene, graphene oxide, and nanopatterned graphene, which showed excellent potential in the explosive trace detection 94 . In particular, poly(dendrimers) were reported for identifying nitro‐based explosives 95 . Furthermore, a promising platform of field‐effect transistors based on silicon nanowires (SiNWs) has been developed for selective and sensitive identification 96 .…”
Section: Hazardous Chemicalsmentioning
confidence: 99%
“…Graphene‐based sensors were demonstrated that platforms were designed to incorporate pristine graphene, graphene oxide, and nanopatterned graphene, which showed excellent potential in the explosive trace detection 94 . In particular, poly(dendrimers) were reported for identifying nitro‐based explosives 95 . Furthermore, a promising platform of field‐effect transistors based on silicon nanowires (SiNWs) has been developed for selective and sensitive identification 96 .…”
Section: Hazardous Chemicalsmentioning
confidence: 99%
“…[ 3,4 ] Thus, research of high energy and insensitivity of explosives has attracted some attention. [ 5,6 ] 1,3,5‐Triamino‐2,4,6‐trinitrobenzene (TATB) is a thermally stable, insensitive high explosive that is favorable for preparing insensitive munitions. TATB has attracted great attention and is widely used in the field of EMs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These monodispersed dendritic polymers exhibit wide applications in the field of catalysis, sensing, molecular electronics, photonics, fluorescence, and therapeutics. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] After Tomalia's first report on poly(amidoamine) (PAMAM) dendrimers in 1985, 20 many research groups have reported the synthesis dendritic macromolecules using ether, ester, carbosilane, amide, and alkyne linkages. [21][22][23][24][25][26][27][28][29][30][31][32][33] Nevertheless, very few have reported the synthesis of dendrimers having urethane linkage.…”
Section: Introductionmentioning
confidence: 99%